2022
DOI: 10.1086/717893
|View full text |Cite
|
Sign up to set email alerts
|

Welfare Reform and the Intergenerational Transmission of Dependence

Abstract: AUGUST 2017 IZA DP No. 10942 Welfare Reform and the Intergenerational Transmission of Dependence *We estimate the effect of welfare reform on the intergenerational transmission of welfare participation and related economic outcomes using a long panel of mother-daughter pairs over the survey period 1968-2013 in the Panel Study of Income Dynamics. Because states implemented welfare reform at different times starting in 1992, the cross-state variation over time permits us to quasi-experimentally separate out the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 80 publications
4
23
1
Order By: Relevance
“…For example, the same US study by Hartley et al. (2017) that found strong within program effects, did not find any effects on welfare use in general for adult daughters of affected mothers. The reforms also did not appear to reduce other undesirable economic outcomes such as unemployment, poverty, and low human capital attainment.…”
Section: The Intergenerational Impacts Of Changes In Welfare Policy D...mentioning
confidence: 89%
See 4 more Smart Citations
“…For example, the same US study by Hartley et al. (2017) that found strong within program effects, did not find any effects on welfare use in general for adult daughters of affected mothers. The reforms also did not appear to reduce other undesirable economic outcomes such as unemployment, poverty, and low human capital attainment.…”
Section: The Intergenerational Impacts Of Changes In Welfare Policy D...mentioning
confidence: 89%
“…Studies that examine the impact of childhood exposure to welfare on other later life outcomes, such as across (as opposed to within) program participation, schooling, employment and health, tend to arrive at different conclusions. For example, the same US study by Hartley et al (2017) that found strong within program effects, did not find any effects on welfare use in general for adult daughters of affected mothers. The reforms also did not appear to reduce other undesirable economic outcomes such as unemployment, poverty, and low human capital attainment.…”
Section: 1mentioning
confidence: 93%
See 3 more Smart Citations